2007
DOI: 10.1107/s1600536807053561
|View full text |Cite
|
Sign up to set email alerts
|

1-Ferrocenylmethyl-2-phenyl-1H-1,3-benzimidazole

Abstract: In the title molecule, [Fe(C5H5)(C19H15N2)], the five‐membered C3N2 imidazole ring forms dihedral angles of 84.71 (13) and 52.12 (11)°, respectively, with the substituted cyclopentadienyl and phenyl rings. In the crystal structure, in addition to a weak C—H...N interaction, there is a modest C—H...π(ring) interaction involving a C—H group of the unsubstituted cyclopentadienyl ring and the imidazole ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The two exocyclic C-C-O angles at atom C33 (Table 2) differ by almost 10 . This behaviour seems to be typical for methoxyarene systems where the methoxy C atoms lies in, or close to, the plane of the arene ring (Seip & Seip, 1973;Ferguson et al, 1996;Gallagher et al, 2001Gallagher et al, , 2004Peralta et al, 2007;Cuervo et al, 2009), and a similar pattern is observed for the exocyclic C-C-O angles at atom C44, consistent with the location of atom C34 close to the plane of the pyridine ring, as noted above. By contrast, the exocyclic C-C-O angles at atom C34 are almost identical, typical of such angles where the -C atom of the alkoxy substituent is significantly displaced from the plane of the adjacent ring (Peralta et al, 2007;Cuervo et al, 2009).…”
Section: Figuresupporting
confidence: 78%
“…The two exocyclic C-C-O angles at atom C33 (Table 2) differ by almost 10 . This behaviour seems to be typical for methoxyarene systems where the methoxy C atoms lies in, or close to, the plane of the arene ring (Seip & Seip, 1973;Ferguson et al, 1996;Gallagher et al, 2001Gallagher et al, , 2004Peralta et al, 2007;Cuervo et al, 2009), and a similar pattern is observed for the exocyclic C-C-O angles at atom C44, consistent with the location of atom C34 close to the plane of the pyridine ring, as noted above. By contrast, the exocyclic C-C-O angles at atom C34 are almost identical, typical of such angles where the -C atom of the alkoxy substituent is significantly displaced from the plane of the adjacent ring (Peralta et al, 2007;Cuervo et al, 2009).…”
Section: Figuresupporting
confidence: 78%
“…Data collection: CrystalClear (Rigaku, 2005); cell refinement: CrystalClear; data reduction: CrystalClear; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL/PC (Sheldrick, 2008); software used to prepare material for publication: SHELXL97. It has been generally accepted that benzimidazole systems continue to attract much attention due to applications in : chemical synthesis, structural science, applied biological and coordination chemistry (Gallagher et al, 2001;Huang et al, 2003;Kazak et al, 2006). We report here the crystal structure of the title compound (Fig.1).…”
Section: Methodsmentioning
confidence: 99%
“…For the crystal structures of related compounds, see: Li et al (1998); Gallagher et al (2001); ; Huang et al (2003); Kazak et al (2006). For ring-puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For general background to benzimidazole compounds, see: Zarrinmayeh et al (1998); Gallagher et al (2001); .…”
Section: Related Literaturementioning
confidence: 99%
“…Benzimidazole systems continue to attract much attention in chemical synthesis, structural science and applied medicinal research (Zarrinmayeh, et al,1998;Gallagher et al, 2001;). Here we report the crystal structure of the title compound, 1-(2-benzimidazolyl)-4-nitrobenzene dimethylformamide solvate.…”
Section: S1 Commentmentioning
confidence: 99%